STUDY OF ERROR ESTABLISHMENT IN MILLING MACHINES WITH 5 AXES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
This report examines the accuracy of rotary die processing on a 5 axes machine and a special bolt-disk system. Faults that affect the accuracy and their measurement and reduction within acceptable limits are analyzed. As a result of the measurement, a virtual model of the radial beating of the workpiece relative to the actual axis of rotation of the machine was developed.